Ideologi T-Shirt Bebaskan JRX Sebagai Sebuah Komoditi dan Simbol Perlawanan Terhadap Kekuasaan - Krisna Ari, Ida Ayu Dwita; Kusuma Dewi, Made Ika (Widya Duta: Jurnal Ilmiah Ilmu Agama dan Ilmu Sosial Budaya, 2021)
Clothing has become an important part of the lifestyle and has become a fashion trend in Balinese society. Clothing is very closely related to the human self, through clothing can reveal many things about the identity of the wearer from the appearance reflected how the social status and personality of the wearer. Currently, the t-shirt is a popular clothing used by people from all walks of life because it is easy to clean and the model remains eternal from time to time. T-shirts have several conveniences, apart from being cheap, comfortable to wear, easy to clean, mobile, functional, and can be used as souvenirs, and so on, this makes business people and politicians realize that t-shirts can be used as a gift. an effective and efficient promotional media, apart from being a means of advertising t-shirts, it is also used as a medium to spread political understanding. Of the several functions possessed by the t-shirt, it is related to the function of the t-shirt as a medium for delivering messages and aspirations. Currently, several types of t-shirts have emerged that carry the aspirations of several groups of people who empathize with the case that befell the drummer for the Superman Is Dead band, I Gede Ari Astina, or who is familiarly called Jerink, later shortened to JRX. Regarding this case, many JRX sympathizers thought that he did not deserve to be punished, without holding mediation to bridge the problem between JRX and IDI Bali which he criticized, but the JRX case went straight to the legal process so that it was considered by some groups of society as an act. silence the aspirations of the small people who try to voice injustice in this country, therefore several individual formation practices have emerged that determine their common social orientation, this community movement group has the same ideology and so that they can act structurally so that it is in line with their ideology. stretcher, then in the process of marking the ideology, several t-shirt designs emerged with the theme â€œfree JRXâ€ with various variants, designs, colors that emerged from several groups that had the same ideology